PELATIHAN PEMBUATAN HAND SANITIZER UNTUK MENCEGAH PENULARAN COVID 19 PADA KADER DI DESA PADEMAWU BARAT - Yayuk Eliyana; Kinanatul Qomariyah; Sari Pratiwi Apidianti (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Covid 19 can be transmitted from human to human through coughing / sneezing, people most at risk of contracting the disease are people who are in direct contact with covid 19 patients. To break the chain of transmission of covid 19 the role of community members is needed for example by maintaining distance, quarantine of the region, maintaining environmental health and hygiene, wearing masks, washing hands, adequate rest so that immunity is maintained and using hand sanitizer. The use of hand sanitizer is very important to prevent the transmission of covid 19. Hand sanitizers have the ability to kill viruses, but due to the high market needs make hand sanitizers difficult to find in the market. Utilization of natural ingredients aloe vera and basil in the manufacture of hand sanitizer can be a solution to meet the needs of hand sanitizer. Hand sanitizer training activities to cadres were held at West Pademawu Village Hall. The implementation of this activity is expected by cadres to be able to socialize to the community, so that the need for hand sanitizer can be met.